Stochastic resonance of a high-order-degradation bistable system and its application in fault diagnosis with variable speed condition. (1st March 2023) - Xu, Haitao; Zhou, Shengxi; Yang, Tao
Highlights: The stochastic resonance of the high-order-degradation bistable system (HBSR) is theoretically analyzed. A novel measurement index is proposed to determine the occurrence of the HBSR for fault diagnosis without the prior knowledge. The HBSR can successfully detect the fault types of a rolling element bearing with variable speed condition. Abstract: Rolling element bearings play a critical role in rotating machines with variable speed conditions, and their fault detection has attracted considerable interest from researchers in recent decades. In this paper, a high-order-degradation bistable system is proposed, and the corresponding stochastic resonance (SR) based on a new measurement index is investigated for fault detection with variable speed conditions. It successfully achieves fault detection without prior knowledge. Firstly, the output signal-to-noise ratio (SNR) of the high-order-degradation bistable stochastic resonance (HBSR) is theoretically analyzed using the approximate adiabatic theory. Secondly, a novel measurement index for determining the occurrence of stochastic resonance is proposed. Thirdly, the experimental data are used to validate the efficiency of the proposed nonlinear system and measurement index when the fault types and the actual fault order are unknown. Finally, the ground test data from a civil aircraft engine is also used to further validate the performance of the HBSR based on the novel measurement index.